2021
DOI: 10.1038/s41589-021-00802-w
|View full text |Cite
|
Sign up to set email alerts
|

Acute pharmacological degradation of Helios destabilizes regulatory T cells

Abstract: The zinc finger transcription factor Helios is critical for maintaining the identity, anergic phenotype, and suppressive activity of regulatory T cells. While it is an attractive target to enhance the efficacy of currently approved immunotherapies, no existing approaches can directly modulate Helios activity or abundance. Here, we report the structure-guided development of small molecules that recruit the E3 ubiquitin ligase substrate receptor Cereblon to Helios, thereby promoting its degradation. Pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 39 publications
4
67
0
Order By: Relevance
“…However, IKZF1 and 3 are broadly expressed in the developing and differentiated immune system and their degradation causes pleiotropic effects 9 . Our studies with DKY709 extend previous work using IMiD analogs capable of degrading IKZF2/4 along with IKZF1/3, which have the potential for confounding effects derived from co-degradation of IKZF1 and IKZF3 34 . In addition to effects in Tregs, this work supports a functional role for IKZF2/4 on Teff cell dysfunction, validating several published reports describing the expression of IKZF2 in dysfunctional Teff cells states 13,14,38 .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, IKZF1 and 3 are broadly expressed in the developing and differentiated immune system and their degradation causes pleiotropic effects 9 . Our studies with DKY709 extend previous work using IMiD analogs capable of degrading IKZF2/4 along with IKZF1/3, which have the potential for confounding effects derived from co-degradation of IKZF1 and IKZF3 34 . In addition to effects in Tregs, this work supports a functional role for IKZF2/4 on Teff cell dysfunction, validating several published reports describing the expression of IKZF2 in dysfunctional Teff cells states 13,14,38 .…”
Section: Discussionsupporting
confidence: 74%
“…2c). Unlike the recently published CRBN:IKZF2(ZF2) structure 34 , CRBN was bound to DKY709:IKZF2(ZF2) in the "open" conformation similarly to the CRBN-IKZF1(ZF2) complex 25 where the IMiD-binding domain (IBD) rotates ~45 degrees relative to the rest of the complex (Extended Data Fig. 2c).…”
Section: Biophysical and Structural Characterizationmentioning
confidence: 65%
“…This IKZF2 degradation is blocked after pretreatment of MLN4924, a neddylation inhibitor of the cullin scaffold in E3 ligases indicating that IKZF2 is a CC-92480 dependent substrate of CUL4 CRBN ligase. Recent studies have shown that IKZF2 degraders (ALV2 and DKY709) can modulate regulatory T-cells activity 58 (clinical trial #NCT03891953). This indicates that compounds with no activity in phenotypic viability screens may provide novel insights when included in degrader target screening in different cell contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Foxp3 , the transcription factor that specifies the Treg cell lineage, essential for Treg cell differentiation and suppressor function and defines the Treg cell lineage 65, 66 . Helios ( IKZF2 ) belongs to the Ikaros transcription factor family, is found critically required to maintain a stable Treg cell phenotype in the inflammatory diseases in recent years 67 . To be noted, studies indicated Helios enhances regulatory T cell function in cooperation with Foxp3 in patients with rheumatoid arthritis 68 .…”
Section: Discussionmentioning
confidence: 99%